ANALISIS PRODUKSI USHATANI BAYAM ORGANIK DI KELOPOK TANI MUTIARA FARM DESA PAGELARAN KECEMATAN PAGELARAN KABUPATEN MALANG - Hidayat Ali (Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2019)
AbstractSpinach production in Indonesia is 134,159 tons with a harvest area of 45.32 ha (BPS Statistics of Holtikutra 2014 production), but it is different from the poor region itself, spinach production is 18 quintals with a land area of 1 ha. This is due to one of them by the factors of production and the perception of farmers. In this study using 30 respondents. In the Mutiara Farm group with the Purposive sampling method. the method used is by using the Logit test while production can be seen from the analysis of production factors using cob-douglass analysis. The results of this study show that the ratio 1.4 means profitable and feasible. On perception analysis shows that gender, age, education and family dependency simultaneously influence the organic spinach farming, while the partial age and family weights have no effect. In the production factor of five variables there are multicoliniarita in the land variable, while the variables of seeds, fertilizers, pest disorders and labor simultaneously affect the production of organic spinach while the partial test of seeds and labor does not significantly affect the production of organic spinach.